Language, Power and Identity: Deciphering Language Hegemony through Bourdieu's Symbolic Power - Rahman, Fadhlur; Asirah, Asirah; Saputra, Nizar; Yuzar, Ella (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study examining language as a complex field of power, rather than merely a neutral means of communication. Every form of language use—whether words, dialects, or accents—contains political, historical, and social connotations that reflect and reinforce power hierarchies. In the era of globalization, the dominance of hegemonic languages such as English, as well as national languages such as Indonesian, has led to the marginalization of minority languages, affecting group identities and shifting cultural landscapes. Using a qualitative approach, this study explores the hidden meanings behind language practices and uncovers the power relations involved. Pierre Bourdieu's theory of symbolic power is used to understand language as a form of social capital that has symbolic value in the structure of society. The analysis compares the context of English hegemony globally and in Indonesia, as well as the position of Indonesian and regional languages in the national sphere. The findings highlight the importance of an additive multilingualism approach in language policy to ensure social justice and equitable distributed linguistic capital. Thus, language is posited not merely as a tool of communication but as a crucial instrument of power in social dynamics. Abstrak Penelitian ini mengkaji bahasa sebagai ranah kekuasaan yang kompleks, bukannya sekadar alat komunikasi netral. Setiap bentuk penggunaan bahasa—baik kata-kata, dialek, maupun aksen—mengandung konotasi politik, historis, dan sosial yang mencerminkan dan memperkuat hierarki kekuasaan. Di era globalisasi sekarang ini, dominasi bahasa-bahasa hegemonik seperti Bahasa Inggris, serta bahasa nasional seperti Indonesia, telah menyebabkan marginalisasi bahasa-bahasa minoritas, yang berdampak pada identitas kelompok dan mengubah lanskap budaya. Dengan pendekatan kualitatif, penelitian ini mengeksplorasi makna tersembunyi di balik praktik bahasa dan mengungkap hubungan kekuasaan yang terlibat. Teori